The scientific argumentative skill analysis reviewed from the science literacy aspect of pre-service teacher - Fina Fakhriyah; Ani Rusilowati; Sunyoto Eko Nugroho; Sigit Saptono; Saiful Ridlo; Budinaini Mindyarto; Endang Susilaningsih (Institute of Advanced Engineering and Science, 2022)
Scientific argumentative skills could encourage the critical thinking skill of college students about scientific phenomena. This research aimed to measure and describe the scientific argumentative skill of the primary school teacher candidates, reviewed from the scientific literacy. This research applied the quantitative method by using a survey typed cross-sectional design. The researchers selected the participants with convenience sampling. The results were 184 college students of even semester of 2020/2021. The applied instrument was the validity process. The data collecting techniques were test and questionnaire assisted with a Google Form. The test instrument consisted of four items. Then, the questionnaire item of the student’s perceptions about the argumentative scientific skills consisted of ten items. The researchers arranged the instruments with the indicators of science literacy-based scientific argumentative skills about biodiversity. The validity results showed that the test and questionnaire instruments were valid, relevant, and reliable to measure the skills. The researchers measured the argumentative scientific skills with Toulmin argumentative pattern (TAP) that was modified. The scientific argumentative skill profiles of the students showed that a percentage of 52% students was at level 3. However, there were no students reaching level 5. The students’ perceptions showed that they were interested in expressing their arguments and confidence while expressing their opinions. The results suggested the science educators prepare teacher candidates with argumentative scientific skills by developing learning innovation. The empowerment strategy by using scientific argumentation measurement is essential to apply to create better primary school teacher candidate with 4.0 century skills.